Mitigating vulnerability of adolescent girls via innovative usage of digital technologies: insights from a field trial / Chiranjeeb Ghosh… [et al.] - Ghosh, Chiranjeeb; Paul, Sanjoy; Kuntagod, Nataraj S.; Maitra, Anutosh; Bhat, Indrani (Penerbit UiTM (UiTM Press), 2016)
Adolescents and young adults, between the ages of 10 to 24, comprise approximately 30 percent of India's population. These youths, 365 millionstrong, will shape the future of the nation. Although the Government of India has been spending enormous amount of money in a relentless mannerover decades and the current cohorts of youth are healthier and bettereducated than ever before, the fact of the matter is, vulnerabilities stillpersist for adolescent girls (World Bank, 2014). We argue in this paperthat vulnerability of adolescent girls cannot be dealt with by executingverticals programmes in Education, Health, Nutrition and Protection inisolation rather it needs to be handled by running these programmes in a converged manner. The comprehensive reports and analysis of data across these domains would provide a 360-degree view of individual girls,predicting their potential vulnerability well ahead of time, thereby enabling the stakeholders to intervene and prevent untoward incidents like childmarriage, child labour, child pregnancy, and trafficking among others.Furthermore, insights generated from analysing the data from the field can be used to identify the areas of improvement for the programme as applicable to decision makers at different levels of societal structure starting withvillages to blocks to districts. This paper describes a digital solution called G-Power that comprehensively addresses the above challenges, and shares insights from afield trial carried out in two districts of West Bengal in India.